Tear-resistant flexible composite hose based on ultraviolet light curing and preparation method of tear-resistant flexible composite hose

By using the graphene/block copolymer composite prepared by reacting and polymerizing brominated fluoropolybutadiene with propylene-based graphene and other materials in the ultraviolet curing repair technology, the glass fiber structure layer is impregnated, solving the problem of insufficient multifunctional performance of the photocuring resin in the prior art, and achieving high-performance curing of composite hoses.

CN119661884APending Publication Date: 2025-03-21ZHEJIANG YOUWEI NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411944795.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the existing ultraviolet curing and repair technology, the multifunctional properties of photocuring resins, such as waterproof, corrosion resistance and mechanical properties, have not been effectively improved, limiting the application of materials.

Method used

A tear-resistant flexible composite hose based on ultraviolet light curing is used. The preparation method includes reacting and polymerizing brominated fluoropolybutadiene with a propylene-based graphene and other materials to produce a graphene/block copolymer composite material, and mixing it with a modified unsaturated polyester and a photoinitiator to form a photocuring resin, and finally impregnating the glass fiber structure layer into the resin.

Benefits of technology

This composite hose has good tear resistance and flexibility when it is not light-cured, making it easy to construct; after photocuring, it has excellent waterproof and corrosion resistance and significantly improved mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661884A_ABST
    Figure CN119661884A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of materials, and discloses a tear-resistant flexible composite hose based on ultraviolet light curing and a preparation method thereof. The preparation method comprises the following steps: mixing the epoxy resin modified unsaturated polyester, the graphene / block copolymer composite material and a photoinitiator to prepare light-cured resin, and impregnating the glass fiber structure layer in the light-cured resin to obtain the ultraviolet light curing-based tear-resistant flexible composite hose. The composite hose has good tear resistance and flexibility when not subjected to light curing, construction is convenient, and after light curing, the waterproof and corrosion-resistant performance is excellent, and the mechanical property is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials technology, specifically to a tear-resistant flexible composite hose based on ultraviolet light curing and its preparation method. Background Technology

[0002] Ultraviolet (UV) curing repair technology has become one of the main trenchless repair technologies due to its advantages such as short construction time and small working area. The in-situ curing repair glass fiber lined flexible tube consists of a UV-transmitting inner membrane, a glass fiber-based composite flexible tube, a seepage-proof outer membrane, and a UV-resistant outer membrane. The glass fiber-based composite flexible tube, made of multiple layers of glass fiber fabric impregnated with UV-curing resin, is the core material of UV curing repair technology.

[0003] In existing technologies, UV-curable resins used for UV-curable repair technology include unsaturated polyester resins, vinyl ester resins, and epoxy resins. Unsaturated polyester resins have excellent chemical resistance and physical properties, and were the earliest resins used for in-situ curing repair technology; vinyl ester resins and epoxy resins have strong corrosion resistance, hydrolysis resistance, and high-temperature resistance.

[0004] Existing technologies, such as Chinese patent CN106811129A, disclose a method for preparing glass fiber insulating hoses by photocuring. This method involves coating a glass fiber braided preform with a photocurable resin, which forms a coating after curing, resulting in a hose with good performance. However, this method does not improve the hose's waterproof and other multifunctional properties, thus limiting the application of the material. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a tear-resistant flexible composite hose based on ultraviolet light curing and its preparation method. The composite hose has good tear resistance and flexibility when not light-cured, making it easy to construct. After light curing, it has excellent waterproof and corrosion resistance and good mechanical properties.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a tear-resistant flexible composite hose based on ultraviolet light curing includes the following steps:

[0008] Step (1): Mix brominated fluorinated polybutadiene, cuprous bromide, toluene, N,N,N′,N″,N″-pentamethyldivinyltriamine evenly, add propylene-based graphene and styrene, react, cool after reaction, add ethanol, filter, wash, and dry to obtain graphene / block copolymer composite material.

[0009] Brominated fluorinated polybutadiene is prepared by the following steps:

[0010] S11. Mix tetrafluorophthalic acid, maleic anhydride, propylene glycol, and hydroxyl-terminated polybutadiene, add an antioxidant, and react. After the reaction is complete, raise the temperature and continue the reaction. After the reaction is complete, dehydrate under vacuum to obtain fluorinated hydroxyl-terminated polybutadiene.

[0011] S12. Fluorine-containing hydroxyl-terminated polybutadiene, tetrahydrofuran, and triethylamine are mixed evenly, and 2-bromoisobutyryl bromide is added dropwise. After the addition is complete, the reaction is carried out. After the reaction is complete, ethanol is added, the mixture is filtered, the filtrate is collected, the solvent tetrahydrofuran is removed by rotary evaporation, and the mixture is dried to obtain bromofluorine-containing polybutadiene.

[0012] Propylene-based graphene is prepared by the following steps:

[0013] S21. Mix p-hydroxybenzaldehyde, sarcosine, N,N-dimethylformamide and graphene, disperse by ultrasonication, and react. After the reaction is complete, filter and wash to obtain crude product. Mix crude product with ethanol and disperse by ultrasonication to obtain modified graphene dispersion.

[0014] S22. Triethylamine and modified graphene dispersion are mixed, ultrasonically dispersed, and methacryloyl chloride is added dropwise. After the addition is complete, the reaction is carried out. After the reaction is completed, the mixture is filtered, washed, and dried to obtain propylene-based graphene.

[0015] Step (2): Mix unsaturated polyester, o-diallyl bisphenol A epoxy resin, fluorinated epoxy resin and catalyst, react, and after the reaction is complete, add polymerization inhibitor, styrene and methyl methacrylate, stir and mix, cool, and obtain epoxy resin modified unsaturated polyester.

[0016] The fluorinated epoxy resin is prepared by the following steps:

[0017] 2,3,5,6-Tetrafluoroterephthalic acid, epichlorohydrin, and sodium hydroxide were mixed, and tetramethylammonium bromide was added. After the reaction was completed, the mixture was cooled and purified to obtain a fluorinated epoxy resin.

[0018] An epoxy resin-modified unsaturated polyester, a graphene / block copolymer composite material, and a photoinitiator benzoin ether are mixed evenly to obtain a photocurable resin.

[0019] Step (3): Impregnate the glass fiber structure layer with UV-cured resin. After impregnation, a tear-resistant flexible composite hose based on UV curing is obtained.

[0020] Preferably, in step (1), the mass ratio of brominated fluorinated polybutadiene, cuprous bromide, toluene, N,N,N′,N″,N″-pentamethyldivinyltriamine, propylene graphene, and styrene is 10:0.4-0.5:150-200:0.5-0.6:2-2.2:8-10; the reaction conditions are: reacting at 100-110℃ for 4-6 hours.

[0021] Preferably, in step (1) when preparing brominated fluorinated polybutadiene, the molar ratio of tetrafluorophthalic acid, maleic anhydride, propylene glycol, and hydroxyl-terminated polybutadiene in S11 is 0.5-0.6:0.4-0.5:0.5:0.6-0.7, and the amount of antioxidant added is 0.5-0.6 wt% of the hydroxyl-terminated polybutadiene; the reaction conditions are: reacting at 150-160℃ for 1-1.5h; the heating rate is 2-3℃ / min; and the continued reaction conditions are: continuing the reaction at 195-200℃ until the acid value is lower than 80mgKOH / g.

[0022] Preferably, the antioxidant comprises triphenyl phosphite.

[0023] Preferably, in step (1), when preparing brominated fluorinated polybutadiene, the mass ratio of fluorinated hydroxyl-terminated polybutadiene, tetrahydrofuran, triethylamine, and 2-bromoisobutyryl bromide in S12 is 20:200-250:3-3.5:5.9-6.2; the dropping conditions for 2-bromoisobutyryl bromide are: dropping at 0-2℃ for 20-40 min; and the reaction conditions are: reacting at room temperature for 10-12 h.

[0024] Preferably, in step (1) when preparing propylene-based graphene, in S21 the mass ratio of p-hydroxybenzaldehyde, sarcosine, N,N-dimethylformamide, and graphene is 0.8-1:0.8-1:180-220:0.2; the reaction conditions are: reaction in a nitrogen atmosphere at 130-135℃ for 95-105 h; and the mass ratio of crude product to ethanol is 0.1:280-320.

[0025] Preferably, the washing operation includes: taking the filter cake obtained after filtration and washing it three times with N,N-dimethylformamide, dichloromethane, and ethanol in sequence at 5-8 times the weight of the filter cake.

[0026] Preferably, in step (1) when preparing propylene-based graphene, the volume ratio of methacryloyl chloride, triethylamine, and modified graphene dispersion in S22 is 0.8-1:1:10-12; the dropping conditions for methacryloyl chloride are: dropping in a nitrogen atmosphere at 0-2℃ for 20-40 min; and the reaction conditions are: reacting at room temperature for 24-28 h.

[0027] Preferably, the washing operation includes: taking the filter cake obtained after filtration and sequentially adding 5-8 times the mass of the filter cake to a 1mol / L aqueous solution of hydrogen chloride, a saturated aqueous solution of sodium bicarbonate, water, and ethanol for washing.

[0028] Preferably, in step (2), the mass ratio of unsaturated polyester, o-diallyl bisphenol A epoxy resin, fluorinated epoxy resin, catalyst, polymerization inhibitor, styrene, and methyl methacrylate is 40:10-15:5-10:0.08-0.1:0.1-0.12:8-10:12-14; the reaction conditions are: reacting at 110-120℃ for 2-3 hours; and the stirring and mixing conditions are: stirring and mixing at 80-90℃ for 0.5-1 hours.

[0029] Preferably, the catalyst comprises hexadecyltrimethylammonium bromide; the polymerization inhibitor comprises hydroquinone.

[0030] Preferably, in step (2), when preparing the fluorinated epoxy resin, the mass ratio of 2,3,5,6-tetrafluorophenylenediol, epichlorohydrin, sodium hydroxide, and tetramethylammonium bromide is 20-21:90-92:16-20:0.9-1; the reaction conditions are: reacting at 60-70℃ for 3-4 hours.

[0031] Preferably, the purification operation includes: taking the reaction product obtained after cooling, washing it with 5-6 times the mass of water until neutral, separating the liquid, taking the organic phase, and removing excess epichlorohydrin by rotary evaporation at 80-90°C.

[0032] Preferably, in step (2): the mass ratio of epoxy resin modified unsaturated polyester, graphene / block copolymer composite material and photoinitiator is 100:5-6:1-1.5; the photoinitiator is benzoin ether.

[0033] Preferably, in step (3): the mass ratio of glass fiber structure layer to UV-cured resin is 3:2-2.5; the vacuum impregnation operation is: vacuum impregnation for 0.5-1h at a vacuum degree of 0.06-0.08MPa and a temperature of 15-20℃; and the wall thickness of the tear-resistant flexible composite hose based on UV curing is 3-3.5mm.

[0034] Preferably, the ultraviolet-cured tear-resistant flexible composite hose is prepared by the method described above.

[0035] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0036] This invention prepares brominated fluorinated polybutadiene, reacts and polymerizes it with propylene-based graphene and styrene to obtain a graphene / block copolymer composite material; after modifying unsaturated polyester with epoxy resin, it is mixed with the graphene / block copolymer composite material and a photoinitiator to obtain a photocurable resin; the glass fiber structural layer is impregnated with the photocurable resin, and the resulting composite hose has good tear resistance and flexibility before photocuring, making it easy to construct; after photocuring, it has excellent waterproof and corrosion resistance and good mechanical properties.

[0037] Hydroxyl-terminated polybutadiene is a liquid rubber with excellent comprehensive properties. This invention utilizes the hydroxyl groups at both ends of hydroxyl-terminated polybutadiene to undergo a copolymerization reaction with tetrafluorophthalic acid, maleic anhydride, and propylene glycol to obtain fluorinated hydroxyl-terminated polybutadiene with fluorinated functional groups and an unsaturated polyester structure. Then, its terminal hydroxyl groups are reacted with 2-bromoisobutyryl bromide to obtain brominated fluorinated polybutadiene, which can be used as an initiator to undergo an atom transfer radical polymerization reaction with propylene-based graphene and styrene to form a graphene / block copolymer composite material.

[0038] Among them, propylene-based graphene is prepared by reacting graphene with p-hydroxybenzaldehyde and sarcosine, modifying the surface of graphene with phenolic hydroxyl groups through a 1,3-dipolar cycloaddition reaction, and then esterifying it with acryloyl chloride. It can participate in atom transfer radical polymerization through carbon-carbon double bonds, so that the block copolymer and graphene are connected by covalent bonds, improving the compatibility of graphene in the matrix. Furthermore, since tetrafluorophthalic acid and maleic anhydride are added during the preparation of fluorinated hydroxyl-terminated polybutadiene, one of the raw materials of graphene / block copolymer composite material, the resulting composite material has excellent hydrophobic and waterproof properties and has an unsaturated polyester structure, which further improves its dispersibility and compatibility in the matrix material.

[0039] This invention utilizes the reaction of 2,3,5,6-tetrafluoroterephthalic acid with epichlorohydrin to obtain a fluorinated epoxy resin, which is then mixed with o-diallyl bisphenol A epoxy resin and an unsaturated polyester. The epoxy groups in the epoxy resin react with the terminal carboxyl groups in the unsaturated polyester. After the reaction, an active monomer is added to obtain an epoxy resin-modified unsaturated polyester.

[0040] The introduction of epoxy resin-based materials eliminates most of the carboxyl groups in the unsaturated polyester, introduces epoxy resin structure and fluorinated hydrophobic functional groups, and improves the thermal stability and hydrophobic properties of the unsaturated polyester. On the other hand, the epoxy resin structure contains hydroxyl groups, which can effectively improve the adhesion between the photocurable resin and the glass fiber structure layer, and improve the mechanical properties of the composite hose. At the same time, the introduction of o-diallyl bisphenol A epoxy resin increases the carbon-carbon double bond content in the matrix resin, which accelerates the photocuring process of the resin, increases the degree of crosslinking, and further improves the waterproof, corrosion-resistant, and tear-resistant properties of the matrix resin after photocuring.

[0041] Glass fiber braided fabrics, after being impregnated with resin and cured, exhibit improved tear resistance by constructing cross-linked structures between the glass fibers. This invention impregnates the glass fiber structural layer with a photocurable resin prepared from a mixture of epoxy-modified unsaturated polyester, graphene / block copolymer composite material, and photoinitiator benzoin ether. The resulting composite hose exhibits excellent tear resistance and flexibility and can be photocured by ultraviolet irradiation. During photocuring, the carbon-carbon double bonds in the epoxy-modified unsaturated polyester and graphene / block copolymer composite material can form cross-linked structures through photosensitive polymerization, further improving the compatibility of the graphene / block copolymer composite material in the matrix. This allows the ordered and selective uniform dispersion of the graphene nanolayer structure in the matrix, serving not only as physical cross-linking points but also increasing the diffusion path of water in the matrix, thereby improving the waterproof, corrosion-resistant, and mechanical properties of the composite hose after photocuring. Attached Figure Description

[0042] Figure 1 This is a process flow diagram of the preparation of tear-resistant flexible composite hose based on ultraviolet light curing in this invention. Detailed Implementation

[0043] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0044] Example 1: This example discloses a method for preparing a tear-resistant flexible composite hose based on ultraviolet light curing, including the following steps:

[0045] Step (1): Brominated fluorinated polybutadiene, cuprous bromide, toluene, N,N,N′,N″,N″-pentamethyldivinyltriamine are mixed evenly, and propylene-based graphene and styrene are added. The mass ratio of brominated fluorinated polybutadiene, cuprous bromide, toluene, N,N,N′,N″,N″-pentamethyldivinyltriamine, propylene-based graphene, and styrene is 10:0.4:150:0.5:2:8. The mixture is reacted at 100℃ for 6 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain the crude product. Ethanol with a mass of 8 times that of the crude product is added, the mixture is filtered, the filter cake is taken, and ethanol with a mass of 5 times that of the filter cake is added for washing. The mixture is dried at 40℃ for 28 hours to obtain the graphene / block copolymer composite material.

[0046] Brominated fluorinated polybutadiene is prepared by the following steps:

[0047] S11. Tetrafluorophthalic acid, maleic anhydride, propylene glycol, and hydroxyl-terminated polybutadiene are mixed in a molar ratio of 0.5:0.5:0.5:0.6. Triphenyl phosphite, an antioxidant, is added at a concentration of 0.5 wt% of the hydroxyl-terminated polybutadiene. The mixture is reacted at 150°C for 1.5 h. After the reaction, the temperature is increased at a rate of 2°C / min and the reaction is continued at 195°C until the acid value is below 80 mg KOH / g. After the reaction, the mixture is dehydrated under vacuum for 1 h to obtain fluorinated hydroxyl-terminated polybutadiene.

[0048] S12. Fluorine-terminated hydroxyl-terminated polybutadiene, tetrahydrofuran, and triethylamine are mixed evenly. 2-Bromoisobutyryl bromide is added dropwise at 0°C for 20 min. The mass ratio of fluorine-terminated hydroxyl-terminated polybutadiene, tetrahydrofuran, triethylamine, and 2-bromoisobutyryl bromide is 20:200:3:5.9. After the addition is complete, the reaction is carried out at room temperature for 10 h. After the reaction is completed, a crude product is obtained. Ethanol with a mass of 5 times that of the crude product is added. The mixture is filtered, and the filtrate is removed by rotary evaporation at 30°C to remove the solvent tetrahydrofuran. The filtrate is then dried at 40°C for 24 h to obtain brominated fluorinated polybutadiene.

[0049] Propylene-based graphene is prepared by the following steps:

[0050] S21. P-hydroxybenzaldehyde, sarcosine, N,N-dimethylformamide, and graphene were mixed in a mass ratio of 0.9:0.9:200:0.2 and ultrasonically dispersed for 20 min. The mixture was then reacted at 130°C under a nitrogen atmosphere for 100 h. After the reaction was completed, the mixture was filtered, and the filter cake was collected. Six times the mass of the filter cake was added to N,N-dimethylformamide, dichloromethane, and ethanol, and the mixture was washed three times to obtain the crude product. The crude product was then mixed with ethanol in a mass ratio of 0.1:300 and ultrasonically dispersed for 6 min to obtain the modified graphene dispersion.

[0051] S22. Triethylamine and modified graphene dispersion were mixed and ultrasonically dispersed for 6 min. Methacryl chloride was added dropwise under a nitrogen atmosphere at 1 °C for 30 min. The volume ratio of methacryl chloride, triethylamine, and modified graphene dispersion was 0.9:1:11. After the addition was complete, the mixture was reacted at room temperature for 26 h. After the reaction was completed, the mixture was filtered, and the filter cake was washed sequentially with 1 mol / L hydrogen chloride aqueous solution, saturated sodium bicarbonate aqueous solution, water, and ethanol, which were then added 6 times the mass of the filter cake. The mixture was dried at 65 °C for 12 h to obtain propylene-based graphene.

[0052] Step (2): Unsaturated polyester, o-diallyl bisphenol A epoxy resin, fluorinated epoxy resin, and catalyst hexadecyltrimethylammonium bromide are mixed and reacted at 110°C for 3 hours. After the reaction is completed, hydroquinone, styrene and methyl methacrylate are added as polymerization inhibitors. The mass ratio of unsaturated polyester, o-diallyl bisphenol A epoxy resin, fluorinated epoxy resin, hexadecyltrimethylammonium bromide, hydroquinone, styrene and methyl methacrylate is 40:15:5:0.08:0.1:8:14. The mixture is stirred and mixed at 80°C for 1 hour and then cooled to obtain epoxy resin modified unsaturated polyester.

[0053] The fluorinated epoxy resin is prepared by the following steps:

[0054] 2,3,5,6-Tetrafluoroterephthalic acid, epichlorohydrin, and sodium hydroxide were mixed, and tetramethylammonium bromide was added. The mass ratio of 2,3,5,6-tetrafluoroterephthalic acid, epichlorohydrin, sodium hydroxide, and tetramethylammonium bromide was 20:90:16:0.9. The mixture was reacted at 60°C for 4 hours. After the reaction was completed, the mixture was cooled to room temperature to obtain the reaction product. The product was washed with water at 5 times its mass until neutral. The mixture was separated, and the organic phase was removed by rotary evaporation at 80°C to remove excess epichlorohydrin, thus obtaining a fluorinated epoxy resin.

[0055] Epoxy resin-modified unsaturated polyester, graphene / block copolymer composite material, and photoinitiator benzoin ether were mixed uniformly at a mass ratio of 100:5:1 to obtain a photocurable resin.

[0056] Step (3): Impregnate the glass fiber structure layer with UV-cured resin. After impregnation, a tear-resistant flexible composite hose with a wall thickness of 3 mm based on UV curing is obtained.

[0057] The mass ratio of the glass fiber structural layer to the photocurable resin is 3:2; the vacuum impregnation operation is as follows: vacuum impregnation for 1 hour at a vacuum degree of 0.06 MPa and a temperature of 15°C.

[0058] Example 2: This example discloses a method for preparing a tear-resistant flexible composite hose based on ultraviolet light curing, including the following steps:

[0059] Step (1): Mix brominated fluorinated polybutadiene, cuprous bromide, toluene, N,N,N′,N″,N″-pentamethyldivinyltriamine evenly, add propylene-based graphene and styrene. The mass ratio of brominated fluorinated polybutadiene, cuprous bromide, toluene, N,N,N′,N″,N″-pentamethyldivinyltriamine, propylene-based graphene, and styrene is 10:0.42:180:0.53:2.05:8.5. React at 105℃ for 5 hours. After the reaction is completed, cool to room temperature to obtain the crude product. Add 8 times the mass of the crude product to ethanol, filter, take the filter cake, wash with 6 times the mass of the filter cake to ethanol, and dry at 45℃ for 26 hours to obtain the graphene / block copolymer composite material.

[0060] The preparation of propylene-based graphene is the same as in Example 1; brominated fluorinated polybutadiene is prepared by the following steps:

[0061] S11. Tetrafluorophthalic acid, maleic anhydride, propylene glycol, and hydroxyl-terminated polybutadiene are mixed in a molar ratio of 0.53:0.43:0.5:0.63. Triphenyl phosphite, an antioxidant, is added at an amount of 0.5 wt% of the hydroxyl-terminated polybutadiene. The mixture is reacted at 155°C for 1 hour. After the reaction, the temperature is increased at a rate of 2.5°C / min and the reaction continues at 195°C until the acid value is below 80 mg KOH / g. After the reaction, the mixture is dehydrated under vacuum for 1.5 hours to obtain fluorinated hydroxyl-terminated polybutadiene.

[0062] S12. Fluorine-terminated hydroxyl-terminated polybutadiene, tetrahydrofuran, and triethylamine are mixed evenly. 2-Bromoisobutyryl bromide is added dropwise at 1°C for 30 min. The mass ratio of fluorine-terminated hydroxyl-terminated polybutadiene, tetrahydrofuran, triethylamine, and 2-bromoisobutyryl bromide is 20:230:3.1:6. After the addition is complete, the reaction is carried out at room temperature for 11 h. After the reaction is completed, a crude product is obtained. Ethanol with a mass of 6 times that of the crude product is added. The mixture is filtered, and the filtrate is removed by rotary evaporation at 40°C to remove the solvent tetrahydrofuran. The filtrate is then dried at 45°C for 20 h to obtain brominated fluorinated polybutadiene.

[0063] Step (2): Unsaturated polyester, o-diallyl bisphenol A epoxy resin, fluorinated epoxy resin, and catalyst hexadecyltrimethylammonium bromide are mixed and reacted at 115°C for 2.5 h. After the reaction is completed, hydroquinone, styrene and methyl methacrylate are added as polymerization inhibitors. The mass ratio of unsaturated polyester, o-diallyl bisphenol A epoxy resin, fluorinated epoxy resin, hexadecyltrimethylammonium bromide, hydroquinone, styrene and methyl methacrylate is 40:14:6:0.09:0.11:8.5:13.5. The mixture is stirred and mixed at 85°C for 0.8 h and then cooled to obtain epoxy resin modified unsaturated polyester.

[0064] The fluorinated epoxy resin is prepared by the following steps:

[0065] 2,3,5,6-Tetrafluoroterephthalic acid, epichlorohydrin, and sodium hydroxide were mixed, and tetramethylammonium bromide was added. The mass ratio of 2,3,5,6-tetrafluoroterephthalic acid, epichlorohydrin, sodium hydroxide, and tetramethylammonium bromide was 20.3:90.5:17:0.93. The mixture was reacted at 65°C for 3.5 h. After the reaction was completed, the mixture was cooled to room temperature to obtain the reaction product. The product was washed with water at 5 times its mass until neutral. The mixture was separated, and the organic phase was removed by rotary evaporation at 85°C to remove excess epichlorohydrin, thus obtaining a fluorinated epoxy resin.

[0066] Epoxy resin-modified unsaturated polyester, graphene / block copolymer composite material, and photoinitiator benzoin ether were mixed uniformly at a mass ratio of 100:5.3:1.3 to obtain a photocurable resin.

[0067] Step (3): Impregnate the glass fiber structure layer with UV-cured resin. After impregnation, a tear-resistant flexible composite hose with a wall thickness of 3 mm based on UV curing is obtained.

[0068] The mass ratio of the glass fiber structural layer to the photocurable resin is 3:2; the vacuum impregnation operation is as follows: vacuum impregnation for 0.8 hours at a vacuum degree of 0.07 MPa and a temperature of 18°C.

[0069] Example 3: This example discloses a method for preparing a tear-resistant flexible composite hose based on ultraviolet light curing, including the following steps:

[0070] Step (1): Brominated fluorinated polybutadiene, cuprous bromide, toluene, N,N,N′,N″,N″-pentamethyldivinyltriamine are mixed evenly, and propylene-based graphene and styrene are added. The mass ratio of brominated fluorinated polybutadiene, cuprous bromide, toluene, N,N,N′,N″,N″-pentamethyldivinyltriamine, propylene-based graphene, and styrene is 10:0.45:180:0.55:2.1:9. The reaction is carried out at 105℃ for 5 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain the crude product. Ethanol with a mass of 9 times that of the crude product is added, and the mixture is filtered. The filter cake is washed with ethanol with a mass of 6 times that of the filter cake and dried at 45℃ for 26 hours to obtain the graphene / block copolymer composite material.

[0071] The preparation of propylene-based graphene is the same as in Example 1; brominated fluorinated polybutadiene is prepared by the following steps:

[0072] S11. Tetrafluorophthalic acid, maleic anhydride, propylene glycol, and hydroxyl-terminated polybutadiene are mixed in a molar ratio of 0.55:0.45:0.5:0.65. Triphenyl phosphite, an antioxidant, is added at an amount of 0.5 wt% of the hydroxyl-terminated polybutadiene. The mixture is reacted at 155°C for 1 hour. After the reaction, the temperature is increased at a rate of 2.5°C / min and the reaction continues at 198°C until the acid value is below 80 mg KOH / g. After the reaction, the mixture is dehydrated under vacuum for 1.5 hours to obtain fluorinated hydroxyl-terminated polybutadiene.

[0073] S12. Fluorine-terminated hydroxyl-terminated polybutadiene, tetrahydrofuran, and triethylamine are mixed evenly. 2-Bromoisobutyryl bromide is added dropwise at 1°C for 30 min. The mass ratio of fluorine-terminated hydroxyl-terminated polybutadiene, tetrahydrofuran, triethylamine, and 2-bromoisobutyryl bromide is 20:230:3.3:6.1. After the addition is complete, the reaction is carried out at room temperature for 11 h. After the reaction is complete, a crude product is obtained. Ethanol with a mass of 6 times that of the crude product is added. The mixture is filtered, and the filtrate is removed by rotary evaporation at 40°C to remove the solvent tetrahydrofuran. The filtrate is then dried at 45°C for 20 h to obtain brominated fluorinated polybutadiene.

[0074] Step (2): Unsaturated polyester, o-diallyl bisphenol A epoxy resin, fluorinated epoxy resin, and catalyst hexadecyltrimethylammonium bromide are mixed and reacted at 115°C for 2.5 h. After the reaction is completed, hydroquinone, styrene and methyl methacrylate are added as polymerization inhibitors. The mass ratio of unsaturated polyester, o-diallyl bisphenol A epoxy resin, fluorinated epoxy resin, hexadecyltrimethylammonium bromide, hydroquinone, styrene and methyl methacrylate is 40:13:7:0.09:0.11:9:13. The mixture is stirred and mixed at 85°C for 0.8 h and then cooled to obtain epoxy resin modified unsaturated polyester.

[0075] The fluorinated epoxy resin is prepared by the following steps:

[0076] 2,3,5,6-Tetrafluoroterephthalic acid, epichlorohydrin, and sodium hydroxide were mixed, and tetramethylammonium bromide was added. The mass ratio of 2,3,5,6-tetrafluoroterephthalic acid, epichlorohydrin, sodium hydroxide, and tetramethylammonium bromide was 20.5:91:18:0.95. The mixture was reacted at 65°C for 3.5 h. After the reaction was completed, the mixture was cooled to room temperature to obtain the reaction product. The product was washed with water at 5 times its mass until neutral. The mixture was separated, and the organic phase was removed by rotary evaporation at 85°C to remove excess epichlorohydrin, thus obtaining a fluorinated epoxy resin.

[0077] Epoxy resin-modified unsaturated polyester, graphene / block copolymer composite material, and photoinitiator benzoin ether were mixed uniformly at a mass ratio of 100:5.5:1.3 to obtain a photocurable resin.

[0078] Step (3): Impregnate the glass fiber structure layer with UV-cured resin. After impregnation, a tear-resistant flexible composite hose with a wall thickness of 3.5 mm based on UV curing is obtained.

[0079] The mass ratio of the glass fiber structural layer to the photocurable resin is 2:2.5; the vacuum impregnation operation is as follows: vacuum impregnation for 0.8 h at a vacuum degree of 0.07 MPa and a temperature of 18°C.

[0080] Example 4: This example discloses a method for preparing a tear-resistant flexible composite hose based on ultraviolet light curing, including the following steps:

[0081] Step (1): Brominated fluorinated polybutadiene, cuprous bromide, toluene, N,N,N′,N″,N″-pentamethyldivinyltriamine are mixed evenly, and propylene-based graphene and styrene are added. The mass ratio of brominated fluorinated polybutadiene, cuprous bromide, toluene, N,N,N′,N″,N″-pentamethyldivinyltriamine, propylene-based graphene, and styrene is 10:0.48:180:0.58:2.15:9.5. The reaction is carried out at 110℃ for 5 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain the crude product. Ethanol with a mass of 9 times that of the crude product is added, and the mixture is filtered. The filter cake is washed with ethanol with a mass of 6 times that of the filter cake and dried at 45℃ for 26 hours to obtain the graphene / block copolymer composite material.

[0082] The preparation of propylene-based graphene is the same as in Example 1; brominated fluorinated polybutadiene is prepared by the following steps:

[0083] S11. Tetrafluorophthalic acid, maleic anhydride, propylene glycol, and hydroxyl-terminated polybutadiene are mixed in a molar ratio of 0.58:0.48:0.5:0.68. Triphenyl phosphite, an antioxidant, is added at a concentration of 0.6 wt% of the hydroxyl-terminated polybutadiene. The mixture is reacted at 155°C for 1 hour. After the reaction, the temperature is increased at a rate of 2.5°C / min and the reaction continues at 200°C until the acid value is below 80 mg KOH / g. After the reaction, the mixture is dehydrated under vacuum for 1.5 hours to obtain fluorinated hydroxyl-terminated polybutadiene.

[0084] S12. Fluorine-terminated hydroxyl-terminated polybutadiene, tetrahydrofuran, and triethylamine are mixed evenly. 2-Bromoisobutyryl bromide is added dropwise at 1°C for 30 min. The mass ratio of fluorine-terminated hydroxyl-terminated polybutadiene, tetrahydrofuran, triethylamine, and 2-bromoisobutyryl bromide is 20:230:3.4:6.2. After the addition is complete, the reaction is carried out at room temperature for 11 h. After the reaction is complete, a crude product is obtained. Ethanol with a mass of 6 times that of the crude product is added. The mixture is filtered, and the filtrate is removed by rotary evaporation at 40°C to remove the solvent tetrahydrofuran. The filtrate is then dried at 45°C for 20 h to obtain brominated fluorinated polybutadiene.

[0085] Step (2): Unsaturated polyester, o-diallyl bisphenol A epoxy resin, fluorinated epoxy resin, and catalyst hexadecyltrimethylammonium bromide are mixed and reacted at 115°C for 2.5 h. After the reaction is completed, hydroquinone, styrene and methyl methacrylate are added as polymerization inhibitors. The mass ratio of unsaturated polyester, o-diallyl bisphenol A epoxy resin, fluorinated epoxy resin, hexadecyltrimethylammonium bromide, hydroquinone, styrene and methyl methacrylate is 40:12:8:0.09:0.11:9.5:12.5. The mixture is stirred and mixed at 85°C for 0.8 h and then cooled to obtain epoxy resin modified unsaturated polyester.

[0086] The fluorinated epoxy resin is prepared by the following steps:

[0087] 2,3,5,6-Tetrafluoroterephthalic acid, epichlorohydrin, and sodium hydroxide were mixed, and tetramethylammonium bromide was added. The mass ratio of 2,3,5,6-tetrafluoroterephthalic acid, epichlorohydrin, sodium hydroxide, and tetramethylammonium bromide was 20.8:91.5:19:0.98. The mixture was reacted at 65°C for 3.5 h. After the reaction was completed, the mixture was cooled to room temperature to obtain the reaction product. The product was washed with water at 5 times its mass until neutral. The mixture was separated, and the organic phase was removed by rotary evaporation at 85°C to remove excess epichlorohydrin, thus obtaining a fluorinated epoxy resin.

[0088] Epoxy resin-modified unsaturated polyester, graphene / block copolymer composite material, and photoinitiator benzoin ether were mixed uniformly at a mass ratio of 100:5.8:1.3 to obtain a photocurable resin.

[0089] Step (3): Impregnate the glass fiber structure layer with UV-cured resin. After impregnation, a tear-resistant flexible composite hose with a wall thickness of 3.5 mm based on UV curing is obtained.

[0090] The mass ratio of the glass fiber structural layer to the photocurable resin is 3:2.5; the vacuum impregnation operation is as follows: vacuum impregnation for 0.8 h at a vacuum degree of 0.07 MPa and a temperature of 18°C.

[0091] Example 5: This example discloses a method for preparing a tear-resistant flexible composite hose based on ultraviolet light curing, including the following steps:

[0092] Step (1): Mix brominated fluorinated polybutadiene, cuprous bromide, toluene, N,N,N′,N″,N″-pentamethyldivinyltriamine evenly, add propylene-based graphene and styrene. The mass ratio of brominated fluorinated polybutadiene, cuprous bromide, toluene, N,N,N′,N″,N″-pentamethyldivinyltriamine, propylene-based graphene, and styrene is 10:0.5:200:0.6:2.2:10. React at 110℃ for 4 hours. After the reaction is completed, cool to room temperature to obtain the crude product. Add 10 times the mass of the crude product to ethanol, filter, take the filter cake, wash with 8 times the mass of the filter cake to ethanol, and dry at 50℃ for 24 hours to obtain the graphene / block copolymer composite material.

[0093] The preparation of propylene-based graphene is the same as in Example 1; brominated fluorinated polybutadiene is prepared by the following steps:

[0094] S11. Tetrafluorophthalic acid, maleic anhydride, propylene glycol, and hydroxyl-terminated polybutadiene are mixed in a molar ratio of 0.6:0.4:0.5:0.7. Triphenyl phosphite, an antioxidant, is added at a concentration of 0.6 wt% of the hydroxyl-terminated polybutadiene. The mixture is reacted at 160°C for 1 hour. After the reaction, the temperature is increased at a rate of 3°C / min and the reaction is continued at 200°C until the acid value is below 80 mg KOH / g. After the reaction, the mixture is dehydrated under vacuum for 2 hours to obtain fluorinated hydroxyl-terminated polybutadiene.

[0095] S12. Fluorine-terminated hydroxyl-terminated polybutadiene, tetrahydrofuran, and triethylamine are mixed evenly. 2-Bromoisobutyryl bromide is added dropwise at 2°C for 40 min. The mass ratio of fluorine-terminated hydroxyl-terminated polybutadiene, tetrahydrofuran, triethylamine, and 2-bromoisobutyryl bromide is 20:250:3.5:6.2. After the addition is complete, the reaction is carried out at room temperature for 12 h. After the reaction is complete, a crude product is obtained. Ethanol with a mass of 8 times that of the crude product is added. The mixture is filtered, and the filtrate is removed by rotary evaporation at 50°C to remove the solvent tetrahydrofuran. The filtrate is then dried at 50°C for 18 h to obtain brominated fluorinated polybutadiene.

[0096] Step (2): Unsaturated polyester, o-diallyl bisphenol A epoxy resin, fluorinated epoxy resin, and catalyst hexadecyltrimethylammonium bromide are mixed and reacted at 120°C for 2 hours. After the reaction is completed, hydroquinone, styrene and methyl methacrylate are added as polymerization inhibitors. The mass ratio of unsaturated polyester, o-diallyl bisphenol A epoxy resin, fluorinated epoxy resin, hexadecyltrimethylammonium bromide, hydroquinone, styrene and methyl methacrylate is 40:10:10:0.1:0.12:10:12. The mixture is stirred and mixed at 90°C for 0.5 hours and then cooled to obtain epoxy resin modified unsaturated polyester.

[0097] The fluorinated epoxy resin is prepared by the following steps:

[0098] 2,3,5,6-Tetrafluoroterephthalic acid, epichlorohydrin, and sodium hydroxide were mixed, and tetramethylammonium bromide was added. The mass ratio of 2,3,5,6-tetrafluoroterephthalic acid, epichlorohydrin, sodium hydroxide, and tetramethylammonium bromide was 21:92:20:1. The mixture was reacted at 70°C for 3 hours. After the reaction was completed, the mixture was cooled to room temperature to obtain the reaction product. The product was washed with 6 times its mass of water until neutral. The mixture was separated, and the organic phase was removed by rotary evaporation at 90°C to remove excess epichlorohydrin, thus obtaining a fluorinated epoxy resin.

[0099] Epoxy resin-modified unsaturated polyester, graphene / block copolymer composite material, and photoinitiator benzoin ether were mixed uniformly at a mass ratio of 100:6:1.5 to obtain a photocurable resin.

[0100] Step (3): Impregnate the glass fiber structure layer with UV-cured resin. After impregnation, a tear-resistant flexible composite hose with a wall thickness of 3.5 mm based on UV curing is obtained.

[0101] The mass ratio of the glass fiber structural layer to the photocurable resin is 3:2.5; the vacuum impregnation operation is as follows: vacuum impregnation for 0.5 h at a vacuum degree of 0.08 MPa and a temperature of 20°C.

[0102] Comparative Example 1

[0103] This comparative example discloses a method for preparing a composite flexible tube, comprising the following steps:

[0104] Step (1): Unsaturated polyester, o-diallyl bisphenol A epoxy resin, fluorinated epoxy resin, and catalyst hexadecyltrimethylammonium bromide are mixed and reacted at 110°C for 3 hours. After the reaction is completed, hydroquinone, styrene and methyl methacrylate are added as polymerization inhibitors. The mass ratio of unsaturated polyester, o-diallyl bisphenol A epoxy resin, fluorinated epoxy resin, hexadecyltrimethylammonium bromide, hydroquinone, styrene and methyl methacrylate is 40:15:5:0.08:0.1:8:14. The mixture is stirred and mixed at 80°C for 1 hour and then cooled to obtain epoxy resin modified unsaturated polyester.

[0105] The fluorinated epoxy resin is prepared by the following steps:

[0106] 2,3,5,6-Tetrafluoroterephthalic acid, epichlorohydrin, and sodium hydroxide were mixed, and tetramethylammonium bromide was added. The mass ratio of 2,3,5,6-tetrafluoroterephthalic acid, epichlorohydrin, sodium hydroxide, and tetramethylammonium bromide was 20:90:16:0.9. The mixture was reacted at 60°C for 4 hours. After the reaction was completed, the mixture was cooled to room temperature to obtain the reaction product. The product was washed with water at 5 times its mass until neutral. The mixture was separated, and the organic phase was removed by rotary evaporation at 80°C to remove excess epichlorohydrin, thus obtaining a fluorinated epoxy resin.

[0107] Epoxy resin-modified unsaturated polyester and photoinitiator benzoin ether were mixed evenly at a mass ratio of 100:1 to obtain a photocurable resin.

[0108] Step (2): Impregnate the glass fiber structure layer with light-cured resin. After impregnation, a composite hose with a wall thickness of 3 mm is obtained.

[0109] The mass ratio of the glass fiber structural layer to the photocurable resin is 3:2; the vacuum impregnation operation is as follows: vacuum impregnation for 1 hour at a vacuum degree of 0.06 MPa and a temperature of 15°C.

[0110] Comparative Example 2

[0111] This comparative example discloses a method for preparing a composite flexible tube, comprising the following steps:

[0112] Step (1): Brominated fluorinated polybutadiene, cuprous bromide, toluene, N,N,N′,N″,N″-pentamethyldivinyltriamine are mixed evenly, and propylene-based graphene and styrene are added. The mass ratio of brominated fluorinated polybutadiene, cuprous bromide, toluene, N,N,N′,N″,N″-pentamethyldivinyltriamine, propylene-based graphene, and styrene is 10:0.4:150:0.5:2:8. The mixture is reacted at 100℃ for 6 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain the crude product. Ethanol with a mass of 8 times that of the crude product is added, the mixture is filtered, the filter cake is taken, and ethanol with a mass of 5 times that of the filter cake is added for washing. The mixture is dried at 40℃ for 28 hours to obtain the graphene / block copolymer composite material.

[0113] The preparation of propylene-based graphene is the same as in Example 1; brominated fluorinated polybutadiene is prepared by the following steps:

[0114] S11. Tetrafluorophthalic acid, maleic anhydride, propylene glycol, and hydroxyl-terminated polybutadiene are mixed in a molar ratio of 0.5:0.5:0.5:0.6. Triphenyl phosphite, an antioxidant, is added at a concentration of 0.5 wt% of the hydroxyl-terminated polybutadiene. The mixture is reacted at 150°C for 1.5 h. After the reaction, the temperature is increased at a rate of 2°C / min and the reaction is continued at 195°C until the acid value is below 80 mg KOH / g. After the reaction, the mixture is dehydrated under vacuum for 1 h to obtain fluorinated hydroxyl-terminated polybutadiene.

[0115] S12. Fluorine-terminated hydroxyl-terminated polybutadiene, tetrahydrofuran, and triethylamine are mixed evenly. 2-Bromoisobutyryl bromide is added dropwise at 0°C for 20 min. The mass ratio of fluorine-terminated hydroxyl-terminated polybutadiene, tetrahydrofuran, triethylamine, and 2-bromoisobutyryl bromide is 20:200:3:5.9. After the addition is complete, the reaction is carried out at room temperature for 10 h. After the reaction is completed, a crude product is obtained. Ethanol with a mass of 5 times that of the crude product is added. The mixture is filtered, and the filtrate is removed by rotary evaporation at 30°C to remove the solvent tetrahydrofuran. The filtrate is then dried at 40°C for 24 h to obtain brominated fluorinated polybutadiene.

[0116] Step (2): Mix unsaturated polyester, graphene / block copolymer composite material and photoinitiator benzoin ether at a mass ratio of 100:5:1 to obtain photocurable resin;

[0117] Step (3): Impregnate the glass fiber structure layer with light-cured resin. After impregnation, a composite hose with a wall thickness of 3 mm is obtained.

[0118] The mass ratio of the glass fiber structural layer to the photocurable resin is 3:2; the vacuum impregnation operation is as follows: vacuum impregnation for 1 hour at a vacuum degree of 0.06 MPa and a temperature of 15°C.

[0119] In the above examples and comparative examples: N,N,N′,N″,N″-pentamethyldivinyltriamine was from Guangdong Wengjiang Chemical Reagent Co., Ltd., CAS No.: 3030-47-5; tetrafluorophthalic acid was from Alfa Aesar, CAS No.: 652-03-9; hydroxyl-terminated polybutadiene was from Shandong Zibo Qilong Chemical Co., Ltd., with a hydroxyl value of 1.3 mmol / g; 2-bromoisobutyryl bromide was from Alfa Aesar, CAS No.: 20769-85-1; p-hydroxybenzaldehyde was from [unclear - likely a specific source]. Hai Aladdin Biochemical Technology Co., Ltd., CAS No.: 123-08-0; sarcosine from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., CAS No.: 107-97-1; graphene from Beijing Beike New Material Technology Co., Ltd., product name: liquid phase exfoliated nano-graphene sheet, sheet diameter: 10μm, thickness: 10-20 layers; methacryloyl chloride from Shandong Duoju Chemical Co., Ltd., CAS No.: 920-46-7; unsaturated polyester from Changzhou Yunuo Composite Materials Technology Co., Ltd., brand name: neopentyl phthalate unsaturated polyester resin P. 92I-910, o-diallyl bisphenol A epoxy resin is from Qingdao Baichen New Material Technology Co., Ltd., product name o-diallyl bisphenol A epoxy resin (DADGEBA), epoxy value 0.38; 2,3,5,6-tetrafluoroterephthalic acid is from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS number: 92339-07-6; the glass fiber structural layer is made of ECR ​​glass fiber multiaxial stitch braided fabric produced by Zhejiang Lianyang New Material Co., Ltd., which is cut and composited to form a tubular structure, the model of glass fiber multiaxial stitch braided fabric is LT1200.

[0120] Test case

[0121] The composite hoses prepared in the examples and comparative examples were subjected to performance tests. The composite hoses prepared in Examples 1-5 and Comparative Examples 1-2 were cured by UV irradiation for 5 minutes using a UV curing machine under the conditions of input power 400W, wavelength 365nm, and irradiation distance 300mm. After curing, samples 1-7 were obtained respectively. The performance of samples 1-7 was tested, and the specific test results are shown in Tables 1 and 2.

[0122] Table 1

[0123] Sample 1 Sample 2 Sample 3 Sample 4 Sample 5 Sample 6 Sample 7 Tear strength (N / mm) >15 >15 >15 >15 >15 >15 >15

[0124] Table 2

[0125]

[0126]

[0127] The tests for each indicator in Tables 1 and 2 were conducted according to the following standards: flexural strength was determined according to GB / T1449-2005 "Test Method for Flexural Properties of Fiber Reinforced Plastics"; tensile strength was determined according to GB / T1040.4-2006 "Determination of Tensile Properties of Plastics Part 4: Test Conditions for Isotropic and Orthotropic Fiber Reinforced Composite Materials"; and waterproof and corrosion-resistant properties were expressed by the change in flexural strength and were determined according to CJJ / T 210-2014 "Technical Specification for Trenchless Repair and Renewal Engineering of Urban Drainage Pipelines".

[0128] As can be seen from the test results in Tables 1 and 2, the composite hose prepared by this invention has good tear resistance when not light-cured, and excellent waterproof and corrosion resistance, as well as good mechanical properties after light curing.

[0129] This invention involves impregnating a glass fiber structural layer with a photocurable resin prepared by mixing epoxy resin-modified unsaturated polyester, graphene / block copolymer composite material, and photoinitiator benzoin ether. The resulting composite hose exhibits excellent tear resistance and flexibility. This is because the glass fiber braid is cured after impregnation with the resin, and the cross-linking structure between the glass fibers improves the tear resistance of the glass fiber braided composite material.

[0130] Graphene / block copolymer composites exhibit excellent compatibility with the matrix, and the presence of fluorinated hydrophobic functional groups enhances the waterproof performance of the composite hose. Epoxy resin-modified unsaturated polyesters, due to the presence of fluorinated hydrophobic functional groups, exhibit improved hydrophobicity, and the presence of hydroxyl groups in the epoxy resin structure of its molecular chain effectively improves the adhesion between the photocurable resin and the glass fiber structural layer, thereby enhancing the mechanical properties of the composite hose. Simultaneously, the introduction of o-diallyl bisphenol A epoxy resin increases the carbon-carbon double bond content in the matrix resin, accelerating the photocuring process and increasing the degree of crosslinking, further improving the waterproof, corrosion-resistant, and tear-resistant properties of the matrix resin after photocuring.

[0131] During the photocuring process of the composite hose, the carbon-carbon double bonds in the epoxy resin-modified unsaturated polyester and graphene / block copolymer composite material can form a cross-linked structure through photosensitive polymerization, which further improves the compatibility of the graphene / block copolymer composite material in the matrix. This allows the nanolayered structure of graphene to be ordered and selectively dispersed uniformly in the matrix, serving not only as physical cross-linking points but also increasing the diffusion path of water in the matrix. This improves the waterproof, corrosion-resistant, and mechanical properties of the composite hose after photocuring.

[0132] Comparative Example 1 did not add graphene / block copolymer composite material, thus lacking the effect of graphene and brominated fluorinated polybutadiene on improving the waterproof, corrosion-resistant, and mechanical properties of the photocurable resin. Therefore, the waterproof, corrosion-resistant, and mechanical properties of Sample 1 prepared by Comparative Example 1 were all reduced.

[0133] Comparative Example 2's unsaturated polyester did not undergo reaction modification with epoxy resin-based materials, and lacked the effect of o-diallyl bisphenol A epoxy resin and fluorinated epoxy resin in improving the hydrophobicity and mechanical properties of the material. Therefore, the waterproof, corrosion-resistant, and mechanical properties of Sample 2 prepared from Comparative Example 2 were all reduced.

[0134] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a tear-resistant flexible composite hose based on ultraviolet light curing, characterized in that: The following steps are involved: Step (1), uniformly mixing brominated fluorinated polybutadiene, cuprous bromide, toluene, and N,N,N′,N″,N″-pentamethyldivinyltriamine, adding propylene-based graphene and styrene, reacting, cooling after the reaction, adding ethanol, filtering, washing, and drying to obtain a graphene / block copolymer composite material; Step (2), mixing unsaturated polyester, o-bisallyl bisphenol A epoxy resin, fluorine-containing epoxy resin and catalyst, reacting, adding polymerization inhibitor, styrene and methyl methacrylate after the reaction, stirring and mixing, cooling, and obtaining epoxy resin modified unsaturated polyester; The epoxy resin modified unsaturated polyester, the graphene / block copolymer composite material and the photoinitiator are uniformly mixed to obtain a photocurable resin; Step (3), impregnating the glass fiber structure layer with a photocurable resin, and after the impregnation is completed, a tear-resistant flexible composite hose based on ultraviolet light curing is obtained.

2. The method for preparing a tear-resistant flexible composite hose based on ultraviolet light curing according to claim 1, characterized in that: In the step (1), the mass ratio of brominated fluorinated polybutadiene, cuprous bromide, toluene, N,N,N′,N″,N″-pentamethyldiethylenetriamine, acrylic graphene and styrene is 10:0.4-0.5:150-200:0.5-0.6:2-2.2:8-10; and the reaction conditions are: reacting at a temperature of 100-110° C. for 4-6 hours.

3. The method for preparing a tear-resistant flexible composite hose based on ultraviolet light curing according to claim 1, characterized in that: The brominated fluorinated polybutadiene in step (1) is prepared by the following steps: S11, tetrafluorophthalic acid, maleic anhydride, propylene glycol, and hydroxy-terminated polybutadiene are mixed, an antioxidant is added, and the mixture is reacted. After the reaction is completed, the temperature is increased and the reaction is continued. After the reaction is completed, vacuum dehydration is performed to obtain fluorinated hydroxy-terminated polybutadiene; S12. Evenly mix fluorinated hydroxyl-terminated polybutadiene, tetrahydrofuran and triethylamine, and dropwise add 2-bromoisobutyryl bromide. After the dropwise addition is complete, react. After the reaction is complete, add ethanol, filter with suction, take the filtrate, rotary evaporate to remove the solvent tetrahydrofuran, and dry to obtain brominated fluorinated polybutadiene.

4. The method for preparing a tear-resistant flexible composite hose based on ultraviolet light curing according to claim 3, characterized in that: When preparing the brominated fluorinated polybutadiene, in S11, the molar ratio of tetrafluorophthalic acid, maleic anhydride, propylene glycol, and hydroxy-terminated polybutadiene is 0.5-0.6:0.4-0.5:0.5:0.6-0.7, and the amount of antioxidant added is 0.5-0.6wt% of the hydroxy-terminated polybutadiene; the reaction conditions are: reacting at a temperature of 150-160° C. for 1-1.5 hours; the heating rate is 2-3° C. / min; the reaction conditions are: continuing the reaction at a temperature of 195-200° C. until the acid value is less than 80 mgKOH / g; In S12: the mass ratio of fluorinated hydroxyl-terminated polybutadiene, tetrahydrofuran, triethylamine and 2-bromoisobutyryl bromide is 20:200-250:3-3.5:5.9-6.2; the dripping condition of 2-bromoisobutyryl bromide is: dripping at 0-2°C for 20-40 minutes; the reaction condition is: react at room temperature for 10-12 hours.

5. The method for preparing a tear-resistant flexible composite hose based on ultraviolet light curing according to claim 1, characterized in that: The acrylic graphene in step (1) is prepared by the following steps: S21, mixing p-hydroxybenzaldehyde, sarcosine, N,N-dimethylformamide and graphene, dispersing by ultrasonication, reacting, filtering after the reaction, washing to obtain a crude reaction product, mixing the crude reaction product with ethanol, dispersing by ultrasonication, and obtaining a modified graphene dispersion; S22, triethylamine and modified graphene dispersion are mixed, ultrasonically dispersed, methacryloyl chloride is added dropwise, after the addition is complete, reacted, after the reaction is completed, filtered, washed, and dried to obtain propylene-based graphene.

6. The method for preparing a tear-resistant flexible composite hose based on ultraviolet light curing according to claim 5, characterized in that: When preparing the propylene-based graphene, in S21, the mass ratio of p-hydroxybenzaldehyde, sarcosine, N,N-dimethylformamide, and graphene is 0.8-1:0.8-1:180-220:0.2; the reaction conditions are: reacting in a nitrogen atmosphere at a temperature of 130-135° C. for 95-105 hours; the mass ratio of the crude reaction product to ethanol is 0.1:280-320; In S22: the volume ratio of methacryloyl chloride, triethylamine and modified graphene dispersion is 0.8-1:1:10-12; the conditions for adding methacryloyl chloride are: adding for 20-40 minutes at 0-2°C in a nitrogen atmosphere; and the reaction conditions are: reacting at room temperature for 24-28 hours.

7. The method for preparing a tear-resistant flexible composite hose based on ultraviolet light curing according to claim 1, characterized in that: The fluorine-containing epoxy resin in step (2) is prepared by the following steps: Mix 2,3,5,6-tetrafluorophenylenedimethanol, epichlorohydrin and sodium hydroxide, add tetramethylammonium bromide, react, cool and purify after the reaction, and obtain a fluorine-containing epoxy resin; Among them, the mass ratio of 2,3,5,6-tetrafluorophenylenedimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide is 20-21:90-92:16-20:0.9-1; the reaction conditions are: react at a temperature of 60-70°C for 3-4h.

8. The method for preparing a tear-resistant flexible composite hose based on ultraviolet light curing according to claim 1, characterized in that: In the step (2), the mass ratio of unsaturated polyester, o-bisallyl bisphenol A epoxy resin, fluorine-containing epoxy resin, catalyst, polymerization inhibitor, styrene and methyl methacrylate is 40:10-15:5-10:0.08-0.1:0.1-0.12:8-10:12-14; the reaction conditions are: react at a temperature of 110-120° C. for 2-3 hours; the stirring and mixing conditions are: stirring and mixing at a temperature of 80-90° C. for 0.5-1 hour; The mass ratio of the epoxy resin modified unsaturated polyester, the graphene / block copolymer composite material and the photoinitiator is 100:5-6:1-1.5; the photoinitiator is benzoin ethyl ether.

9. The method for preparing a tear-resistant flexible composite hose based on ultraviolet light curing according to claim 1, characterized in that: In the step (3), the mass ratio of the glass fiber structural layer to the light-curing resin is 3:2-2.5; the vacuum impregnation operation is: vacuum impregnation for 0.5-1h at a vacuum degree of 0.06-0.08MPa and a temperature of 15-20°C; the wall thickness of the tear-resistant flexible composite hose based on ultraviolet light curing is 3-3.5mm.

10. A tear-resistant flexible composite hose based on ultraviolet light curing prepared by the method for preparing a tear-resistant flexible composite hose based on ultraviolet light curing according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing glass fiber insulating flexible pipe through photocuring

    CN106811129A